Gender Equality and the Participation of Muslim Women in Education and Work: A Critical Analysis - Shehu, Fatmir (IIUM PRESS, 2015)
Most of today’s writings on women tend to fit them within the frame of discrimination, where they are presented as victims of a male dominated society. Voices of women’s rights proponents are raised to promote gender equality in every aspect of life. However, is that what our society should aim for and to what extent should it carry out this quest? Taking a theoretical approach, this paper looks at women both in educational and work environments. An Islamic perspective is employed to evaluate the general issues throughout the paper, specifically the concept of gender equality. Special reference has been made to selected Qur’anic verses and the Prophetic sayings (Ahadith)dealing with women’s issues. The descriptive and analytical methods have been utilized through the entire discussion. This study concludes that problems faced by contemporary women can be solved by referring to the Divine Word of Allah (s.w.t.), the Qur’an and the Prophetic Sunnah, as well as the Divine Oriented traditions.